EKSPLORASI KONSEP DILATASI ETNOMATEMATIKA PADA BATIK TEMBAKAU JEMBER - Noviani, Dwi; Amalia, Devita; Djamali, M. Fadil (Universitas Insan Budi Utomo, 2021)
Ethnomathematics is a variety of different ways of doing mathematics that takes into account the use of mathematical concepts in the academic system developed in various levels of society while taking into account different goals, where cultural differences will create differences in mathematical practice (how to count, classify, measure , designing buildings or tools, playing and so on). Based on this, this study aims to describe the results of ethnomathematical exploration in Jember tobacco batik. The method of analysis in this study using qualitative methods with an ethnographic approach. Data collection techniques in the form of observation, documentation and interviews. This research was conducted at the House of Batik Rolla Jember and Rezti'z Batik Tegalsari Ambulu Jember. The study was carried out for one week. The results of this study indicate that the ethnomathematics of Jember's typical tobacco motif batik has a mathematical concept in the form of the concept of dilatation.